KETERLIBATAN PELAKSANAAN TUGAS DENGAN DISIPLIN TERHADAP PERATURAN KESEHATAN DAN KESELAMATAN KERJA - Sahlan Asnawi; Mochammad Bachroni (Faculty of Psychology, Universitas Gadjah Mada, 1999)
The aims of this study was to find out the correlation between jobinvolvement and health and safety at work disciplinary. The subject of the research were 97 employees of PT. Mandira Nusantara Bogor. The hypothesis stated that the higher the job involvement, the higher the health and safety at work disciplinary. The result shows that the hypothesis is consistent with the study by using product-moment correlation analysis, with r = .741 and p < .05. The Job-involvement account for 57.7% of the variability of health and safety at work disciplinary. Keywords : job – involvement